A descriptive analysis of the perception and attitude of staff on employment equity in the City of Cape Town Health Directorate - Isaaks, Ruberto Carlo (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPA (School of Public Management and Planning))--Stellenbosch University, 2008.